2021
DOI: 10.1186/s40712-021-00129-3
|View full text |Cite
|
Sign up to set email alerts
|

Friction and contact temperature in dry rolling-sliding contacts with MoS2-bonded and a-C:H:Zr DLC coatings

Abstract: Gearboxes are usually lubricated with oil or grease to reduce friction and wear and to dissipate heat. However, gearbox applications that cannot be lubricated with oil or grease, for example in the space or food industry, are commonly lubricated with solid lubricants. Especially solid lubricants with a lamellar sliding mechanism like graphite and molybdenum disulfide (MoS2) or diamond-like carbon (DLC) coatings can enable very low coefficients of friction. This study investigates the friction and temperature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The object of investigation is a contact between two disks. The contraformal reference setup refers to two disks with external raceways as considered by Hofmann et al (2021). The radii of curvature of the two convex disks are identical with R 1,2 = 40 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The object of investigation is a contact between two disks. The contraformal reference setup refers to two disks with external raceways as considered by Hofmann et al (2021). The radii of curvature of the two convex disks are identical with R 1,2 = 40 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments are performed on a twin-disk tribometer, which was also used for thin-film sensor measurements in hard EHL contacts by Ebner et al [ 21 ] and in dry lubricated contacts by Hofmann et al [ 26 ]. Figure 1 shows a schematic of the mechanical layout of the twin-disk tribometer considered.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical calculations of the temperature distribution in coated EHL contacts from, e.g., Ziegltrum et al [ 2 ] revealed strong temperature gradients within surface coatings. Hofmann et al [ 26 ] applied thin-film sensors to dry lubricated soft-coated rolling-sliding contacts. Beyond rolling–sliding contacts, thin-film sensors have also been investigated for temperature measurement, e.g., in cutting tools [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…They inspected from the results that the 0.2 wt.% polyether amine functionalized graphene oxide composite showed well tribological efficiency. Stefan Hofmann et al [14] investigated the impact of friction and temperature on the surface coating in the rolling-sliding contacts for application in dry lubricated gears. N. Nemati et al [15] researched a composite covering made of Polytetrafluoro Ethylene (PTFE) and graphene oxide to improve frictional behaviour in ambient and increased temperature environments considerably.…”
Section: Introductionmentioning
confidence: 99%